Efficacy of the transjugular approach in endovascular intervention for hemodialysis access comparing with conventional approach. Issue 6 (November 2020) - Lee, Chang Hun; Gwon, Jun Gyo; Jung, Cheol Woong; Cho, Sung Bum
Purpose: Compared with the conventional approach, the benefits of the transjugular approach in endovascular intervention for hemodialysis access avoids complications due to direct puncture and reduces direct radiation exposure to the hands of operator. The aim of this non-inferiority study was to evaluate the efficacy of the transjugular approach in endovascular intervention for hemodialysis access comparing with conventional approach. Methods: We retrospectively assessed endovascular intervention for hemodialysis access performed in our hospital from 2012 to 2016, divided into the conventional approach group and the transjugular approach group. The hemodialysis access survival rate, re-intervention survival rate, and lesion characteristics were comparatively evaluated. Results: We included 223 cases in 118 patients (146 cases with conventional approaches and 77 cases with transjugular approaches). There was a higher incidence of thrombosis with the conventional approach (p < 0.001), however, no significant difference in the hemodialysis access type or main lesion location. The transjugular approach showed either a better hemodialysis access survival rate (p = 0.017) and a trend toward improved re-intervention survival rate (p = 0.098) than the conventional approach. Following classification according to the presence of thrombus, there was no significant difference in either the hemodialysis access survival rate or the re-intervention survival rate between the approaches with or without thrombus. Conclusion: The transjugular approach could be performed in most cases and was similar to the conventional approach in terms of outcomes. The transjugular approach should be considered as an alternative to either replace or use in combination with the conventional approach in endovascular intervention for hemodialysis access.